(untitled) (Journal of Economic Research & Business Administration, 2016)
In the current context of global and domestic challenges, the role of professional public managers increases. The article deals with the image of modern Kazakhstani civil servant from a creative standpoint. The use of such approaches in the science allows for a fresh look at the problem; change the viewing angle and through associations may accept non-stan-dard solutions.